Phylogenetic analysis of Haemaphysalis erinacei Pavesi, 1884 (Acari: Ixodidae) from China, Turkey, Italy and Romania. Issue 1 (December 2016) - Hornok, Sándor; Wang, Yuanzhi; Otranto, Domenico; Keskin, Adem; Lia, Riccardo; Kontschán, Jenő; Takács, Nóra; Farkas, Róbert; Sándor, Attila
Abstract Background Haemaphysalis erinacei is one of the few ixodid tick species for which valid names of subspecies exist. Despite their disputed taxonomic status in the literature, these subspecies have not yet been compared with molecular methods. The aim of the present study was to investigate the phylogenetic relationships ofH. erinacei subspecies, in the context of the first finding of this tick species in Romania. Results After morphological identification, DNA was extracted from five adults ofH. e. taurica (from Romania and Turkey), four adults ofH. e. erinacei (from Italy) and 17 adults ofH. e. turanica (from China). From these samples fragments of the cytochromec oxidase subunit 1 (cox 1) and 16S rRNA genes were amplified via PCR and sequenced. Results showed thatcox 1 and 16S rRNA gene sequence divergences betweenH. e. taurica from Romania andH. e. erinacei from Italy were below 2%. However, the sequence divergences betweenH. e. taurica from Romania andH. e. turanica from China were high (up to 7.3% difference for the 16S rRNA gene), exceeding the reported level of sequence divergence between closely related tick species. At the same time, two adults ofH. e. taurica from Turkey had higher 16S rRNA gene similarity toH. e. turanica from China (up to 97.5%) than toH. e. taurica from Romania (96.3%), but phylogenetically clustered more closely toH. e. taurica than toH. e. turanica . Conclusions This is the first finding ofH. erinacei in Romania, and the first (although preliminary) phylogenetic comparison ofH. erinacei subspecies. Phylogenetic analyses did not support that the threeH. erinacei subspecies evaluated here are of equal taxonomic rank, because the genetic divergence betweenH. e. turanica from China andH. e. taurica from Romania exceeded the usual level of sequence divergence between closely related tick species, suggesting that they might represent different species. Therefore, the taxonomic status of the subspecies ofH. erinacei needs to be revised based on a larger number of specimens collected throughout its geographical range.